DICTATORSHIP AND THEORY (VARLAM CHERKEZISHVILI’S CRITIC OF SOCIAL-DEMOCRATIC MOVEMENT) - Gogatishvili, MIkheil (European Scientific Journal, ESJ, 2016)
The central question on which Varlam Cherkezishvili focuses attention is authoritarian character philosophy of Marx and Engels. This theory in the name of emancipation of person creates most radical totalitarian theory. Varlam Cherkezishvili is one of the founder of the methodological anarchism. The methodological anarchism directed against totalitarian presumptions Marxist ideology. Later anarchist thinkers such as Paul Feyerabend(epistomological anarchism) and Murray Bookchin (sicial anarchism) based their thoughts on the principles methodological of anarchism.